Dual lineage origins contribute to neocortical astrocyte diversity - Jiafeng Zhou; Ilaria Vitali; Sergi Roig-Puiggros; Awais Javed; Iva Cantando; Matteo Puglisi; Paola Bezzi; Denis Jabaudon; Christian Mayer; Riccardo Bocchi (Nature Communications)
Abstract Astrocytes are not a uniform population but exhibit diverse morphological, molecular, and functional characteristics. However, how this diversity originates and becomes establishes during development, remains largely unknown. Here, using single-cell RNA sequencing and spatial transcriptomics, we identify five astrocyte subtypes with unique molecular features, spatial distributions and functions in the mouse neocortex and characterize essential regulators for their formation. Using TrackerSeq to trace clonally related astrocytes, we identify two distinct lineages that give rise to these five subtypes. One lineage derives from Emx1 + radial glial cells that initially generate neurons and later switch to astrocyte production. The other, with minimal neuronal output, predominantly produces a distinct subset of astrocytes marked by Olig2. Olig2 knockout disrupts lineage specification, leading to changes at molecular, morphological and functional levels. These findings shed light on the cellular mechanisms underlying astrocyte diversity, highlighting the presence of multiple radial glial cell subtypes responsible for generating cortical astrocyte subtypes.